A review of high-speed rotating HP turbine heat transfer and cooling studies over the last decade in the Oxford Turbine Research Facility - Falsetti, C; Beard, PF; Cardwell, DN; Chana, KS (ASME International, 2022)
Over the last years, advanced experiments under engine-representative conditions have been performed in the Oxford Turbine Research Facility (OTRF) to obtain high-quality aerothermal data that are essential for developing novel cooling designs and for validating computational models. Thanks to its unique experimental capabilities, the OTRF plays a crucial role in the advancement of HP turbines, which are life limiting components of modern gas turbines due to the harsh high temperature environment. The OTRF continues to be developed for additional capability to achieve more engine-representative conditions. Major upgrades include: (i) a combustor simulator able to produce engine radial and circumferential temperature profiles and inlet swirl simultaneously to study combustor-turbine interaction, (ii) fully film-cooled HP turbine designs and 1.5 stage configurations with a low-turning strut, (iii) novel rotor casing effusion cooling concepts, (iv) an advanced in-shaft data acquisition electronics system. More recently, the enhanced capabilities of additive manufacturing have been used in the facility to investigate the performance of novel blade tips and full annular effusion cooling concepts. This allowed complex cooling features and geometries to be implemented and assessed in the facility. The aero-thermal performance of cooled and uncooled blades for three variants of squealer tip design and a next-generation effusion cooling designs have been recently evaluated.